Dual amylase/glucosidase inhibition, antilipolytic and antiproliferative potential of the aerial parts of Pistacia atlantica, Pistacia lentiscus and Pistacia terebinthus on a obesity related-colorectal cancer cell line panel - Hamlat, Nadjia; Alqaraleh, Moath; Kasabri, Violet; Ahmad Mizher, Hussam Abdeljabar; Hassani, Aicha; Afifi, Fatma; Al Alawi, Sundos; Ouafi, Saida; Khwaldeh, Alia (Sciendo, 2024)
Pistacia species (P. spp) have been used as a treatment for various diseases, including diabetes and inflammation. This study aimed to identify the main components of flavonoids in Pistacia species and evaluate the effect of aqueous extracts of P. spp on pancreatic enzymes and on cancer cells associated with obesity in colon and rectum. HPLC was used to identify the major components of flavonoids. The potent inhibitory effect of Pistacia species against pancreatic α-amylase, α-glucosidase and lipase was examined. The antiproliferative efficacy of the plant extract against several colorectal cancer cell lines were then measured. The main flavonoids component found in Pistacia species are quercetin-3-β-D-glucoside, rutin, kaempferol and vitexin. The starch blockade IC50 (µg/mL) of Pistacia species in a descending order were: P. lentiscus leaves: 1.09±0.01; P. atlantica leaves: 0.96±0.09 and P. atlantica fruits: 0.48±0.02. Pistacia species exerted promising inhibition effect for pancreatic lipase (PL). Besides the aglycones of P. atlantica leaves, all the tested aqueous extracts exerted appreciably novel antiproliferative activity against the tested colorectal cancer cell lines. This study provides useful indication for the Pistacia species as a potential novel therapeutic agent against diabesity and cancer.